A novel approach to a recalcitrant case of psoriatic otitis externa - N. J. McInerney; M. Riglar; P. Casserly (Acta Oto-Laryngologica Case Reports, 2023)
AbstractOtitis externa is a commonly encountered pathology by otorhinolaryngologists, with its incidence reported as 1%. Chronic otitis externa is a relapsing disease, that is often precipitated by a systemic dermatologic pathology, such as allergic contact dermatitis or psoriasis. It can be challenging to treat, as common treatment options can be exhausted, and the underlying disease continues to precipitate infection. We report the case of a 52-year-old gentleman, affected by both psoriasis and long-standing otitis externa which is resistant to all traditional treatments. Due to severe canal narrowing, micro-suctioning was not possible. After exhaustion of all treatment options, we commenced the off-label use of topical Betamethasone Dipropionate 0.064% w/w and Salicylic acid 3.00% w/w, which is typically used topically for psoriasis. After four weeks of Betamethasone Dipropionate/Salicylic acid, our patient returned free from otalgia and otorrhea, with his external auditory canal completely patent and free from infection. This case demonstrates the safe and effective use of Betamethasone Dipropionate/Salicylic acid in the case of recalcitrant psoriatic otitis externa.